Enzyme-linked immunosorbent assay (ELISA) for the detection of hepatitis Be antigen and antibody: report of a field trial. Issue 5 (May 1983) - Supran, E M; Boxall, E H; Craske, J; Hart, R J; Vandervelde, E M; Gardner, P S
Abstract : A field trial of an enzyme-linked immunosorbent assay (ELISA) for the detection of the hepatitis Be markers is reported. It is simple to perform, is designed to be read by eye and does not require any expensive apparatus. When compared with a commercially available RIA kit for the detection of the same markers, ELISA was shown to be as sensitive as RIA for the detection of anti-HBe but slightly less sensitive for the detection of HBeAg. However if all specimens negative for both HBeAg and anti-HBe by ELISA are considered to be potentially infectious, the ELISA should prove to be as useful as RIA for determining the "e" status of HBsAg-positive patients and, therefore, provide a reliable indication of the risk of secondary spread of hepatitis B infection to contacts by needle stick accident, close personal contact or perinatal transmission.